Aspek Linguistik Pada Kasus Pencucian Uang First Travel Dalam Dimensi Teks Fairclough - Inne Pelangi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This paper analyzes the discourse of the news text on the first money laundering case in the perspective of Norman Fairlough. The objectives of this research is to describe the linguistic aspect used in representing the character and the topic of proclamation. The method used in this paper is qualitative descriptive with techniques and strategies of critical discourse analysis model Norman Fairclough. The results show that there are three dimensions in the AWK model of Norman Fairclough: linguistic aspects of abbreviations, acronyms, idioms, foreign terms, discourse-interpreting aspects of nomination discourse.